Penerapan Metode Team Quiz Dalam Pembelajaran Akidah Akhlak Dengan Model NHT (Number Head Together) Dalam Meningkat Semangat Belajar Siswa Di MI Al Hidayah Ca - Alfaroh, Machfudz; Sayekti, Siska Putri (Al Makki Publisher, 2023)
This study investigates the application of the Team Quiz method with the Number Head Together (NHT) model in Akidah Akhlak learning at MI Al Hidayah CA with the aim of increasing student enthusiasm for learning. The results showed that the application of the Team Quiz method with the NHT model significantly improved students' learning spirit, with higher participation, more active involvement, and better understanding of the material. This method encourages students to collaborate in group discussions, work together in teams, and share knowledge and thoughts. Thus, the application of the Team Quiz method with the NHT model is expected to be applied in Akidah Akhlak learning to increase students' enthusiasm for learning.